Goalkeeping in the soccer penalty kick: The dive is coordinated to the kicker's non-kicking leg placement, irrespective of time constraints - Zheng, R.; de Reus, C.; van der Kamp, J. (Human Movement Science, 2021)
Traditionally, goalkeeping in the soccer penalty kick has been studied using video-based technology, in which goalkeepers watched video footage of penalty kicks and indicated perceived ball direction. By omitting the requirement to actually dive or jump to the ball, these studies overlooked how action capabilities constrain goalkeepers' actions. By contrast, we examined whether goalkeeping in the penalty kick is consistent with affordance-based control, that is, whether goalkeepers guide their dive by taking into account their action capabilities (i.e., the time they need to intercept the ball).